Respuestas

2012-11-22T00:14:28+01:00

watch awwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwwww

¡La mejor respuesta!
2012-11-22T00:23:11+01:00

 

sustitucion

4x - y=14


4x=14+y

x=(14+y)/4

 

5x + 2y = 11



5((14+y)/4)+2y=11


(70+5y)/4+2y=11


(70+5y+8y)/4=11


(70+13y)/4=11


70+13y=44


13y=44-70


13y=-26


y=-2



4x - y=14


4x+2=14

4x=14-2


4x=12


x=3




reduccion  suma o resta

 

4x - y=14        (2)

5x + 2y = 11



8x-2y=28

5x + 2y = 11

13x=39


x=3


4x - y=14

4(3)- y=14


12-y=14

-y=14-12

Y=-2